Effects of short-term resistance training on oxidative stress, lipid panel, liver and kidney function in patients with and without type 2 diabetes - Sousa, Caio Victor; Filho, Alberto Sousa Sá; Aguiar, Samuel da Silva; Souza, Guilherme Vinícius; Guerra, Marcelo; Ernesto, Carlos; Guido, Marcelo; Cantão, Elbert; Bezerra, Mairiel Leila de Deus; Inácio, Pedro Augusto; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Resistance training is considered a non-pharmacological treatment for several comorbidities, including type 2 diabetes mellitus (T2D) and other non-communicable diseases that accompany it. Objectives: Investigate the effects of short-term resistance training (RT) in patients with T2D on markers of fasting glycaemia, oxidative stress, liver function parameters, lipid profile and renal function in individuals with and without T2D. Methods: 29 participants were included for final analysis, 16 T2D and 13 non-diabetic (ND). Participants were randomized into an intervention group (T2DEX and NDEX) or control group (T2DCTL or NDCTL). Subjects completed questionnaires about their medical history and were assessed for body composition and blood samples were collected for oxidative stress using Thiobarbituric acid reactive substances (TBARS), fasting blood glucose, lipid panel, liver function and renal function, baseline, 4 weeks and 8 weeks of intervention. This comprised circuit training of approximately 20 minutes (2 sets of 6 resistance training exercises) to be performed 3 times a week. Results: T2DEX showed lower TBARS levels after 8 weeks of training (10.0 ±2.0 vs. 6.8 ±4.2 mmol·L-1; p<0.05). High-density lipoprotein (HDL) was significantly reduced in T2DEX (37.5 ±7.9 vs. 24.8 ±6.0 mg·dL-1) and T2DCTL (34.9 ±6.1 vs. 32 ,0). 3 ±7.6 mg·dL-1) in week 4. Low-density lipoprotein (LDL) (219.2 ±40.5 vs. 130.4 ±49.6 mg·dL-1; p<0.05) and total cholesterol (247.6 ±33.4 vs. 205.8 ± 57.2 mg·dL-1) decreased significantly (p<0.05), on T2DEX after training. Both groups that did not exercise had elevated total cholesterol levels after 8 weeks. Conclusion: Short-term circuit training is effective in promoting benefits in oxidative stress and lipid panel in overweight individuals with DM.